The Use of Cartoon Movie as Teaching Media in Teaching Speaking at SMA Muhammadiyah Sukoharjo - Nurnaningsih, N; Pratiwi, Veronika Unun (Universitas Muhammadiyah Surakarta, 2018)
The research has two objectives of the study, they are: to know the function of cartoon movie in teaching speaking and to reveal application of carton movie to teach speaking skill for Class XI Students Of SMA Muhammadiyah I Sukoharjo. he problems studied in this study are qualitative research. The data collection procedure in this research is observation, and documentation. By using cartoon movies for teaching speaking, students are delighted with the advanced technology of LCD and cartoon movies.: (1) what the purposes or objectives of the study were; (2) how the study was done or methodology; (3) what results were obtained; (4) and the significance of the results. The abstract is important because many journal editors first read the abstract to determine if the entire article is worth reading. The abstract should be less than 250 words!